PENGARUH KOMPETENSI DIGITAL DAN LEARNING & DEVELOPMENT TERHADAP PENCAPAIAN TRANSFORMASI DIGITAL PADA DIREKTORAT JENDERAL PENYELENGGARAAN POS DAN INFORMATIKA KEMENTERIAN KOMUNIKASI DAN INFORMATIKA - Damanhuri Damanhuri; Rina Susanti Hartono (Governance, 2022)
This study aims to find out the direct influence of digital competence, learning and development on the achievement of digital transformation and the joint influence between the two on the achievement of digital transformation. This research is a quantitative descriptive study with a population of employees of the Directorat General of Post and Informatics Operation Ministry Communications and Information. Sampling was carried out using simple random sampling technique. The sample in this study was determined by the non-probability sampling method, while the sampling calculation was calculated using the slovin formula, which amounted to 95 people. Data was collected using observation, questionnaires, and documentation. Test the validity of the instrument using product moment correlation and test the reliability of the instrument using the Cronbach alpha formula.The results showed that: Digital Competence partially has an significant influence on Digital Transformation, Learning and Development partially has a significant effect on Digital Transformation. Digital Competence (X1) and Learning and Development (X2) together have a significant effect towards Digital Transformation (Y), means that the regression model can explain the independent variables as a whole.